A CRITICAL REVIEW OF THE FREE SENIOR HIGH SCHOOL POLICY IN GHANA WITHIN THE FRAMEWORK OF DEVELOPMENT OF CURRICULUM - Acquah, Andrews; Attila , Frank Lamadoku; Yalley, Clarke Ebow (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2024)
Central governments across nations play a leading role in initiating and reforming educational policies to address the evolving needs of their workforces. Education is widely recognised as a cornerstone for societal and global development, making it a national priority. National curriculums are heavily influenced by social demands, technological advancements, national aspirations, and educational trends observed in neighbouring countries. Various assessment techniques have been established to evaluate the effectiveness of educational policies in fulfilling curriculum goals. This study employs Dunn's programme assessment framework to analyse the core elements of Ghana's Free Senior High School policy. The evaluation focuses on key dimensions including effectiveness, efficiency, adequacy (sufficiency), equity (fairness), responsiveness, and appropriateness. The analysis reveals that the policy falls short across all significant dimensions of Dunn's framework. Schools in Ghana face significant challenges such as low educational standards, disparities between urban and rural schools, high student-teacher ratios, overcrowding, resource limitations, and an overall lack of responsiveness to the issues the policy aims to tackle. Policymakers should prioritize targeted support for underserved communities, explore alternative funding models, and incentivize collaboration between public and private educational institutions. To help families navigate the challenges arising from the policy's implementation, the study presents implications and recommendations. Notably, for families to fully benefit from the programme, parental involvement is crucial, and political considerations must not overshadow their children's education.